A study of termite attack in terrace house / Mohd Afendi Mohd Yusof - Mohd Yusof, Mohd Afendi (Faculty of Architecture, Planning and Surveying, 2010)
This research was carried out to determine reason and effects of termite attack in residential building especially in terrace house and overcome with a diagnosis and prognosis that to understand about the characteristic of the kind of defect. Termite damage often goes unnoticed until it is quite extensive. Prevention is better than cure to effectively eliminate termites from causing damage to terrace house, the biology and feeding behavior of termites need to be understand. The major factor that influences the termite attack in this terrace house is a housing estate because there are many block of terrace house in this area. The best treatment is to ensure that the termite attack is not occurring again. Serious attention need to be given by all party so that the causes of termite attack